English Teaching Reading at SMP Advent Surakarta on Descriptive Study 2018/ 2019 Academic Year - Danang Wahyu Nugroho; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2019)
The aim of this study is to describe the process of teaching reading in SMP Advent 2018/2019 and to describe the problem in teaching reading at SMP Advent in the Academic Year of 2018/2019.This research was conducted at the seventh grade students of SMP Advent Surakarta in the Academic Year of 2018/ 2019. The researcher used Descriptive Qualitative Research which was conducted February 2019 at the seventh grade. The research was conducted at seventh grade of SMP Advent Surakarta the researcher found some problems during the teaching reading processed with three meetings of learning process. In analyzing the data, the researcher used qualitative data. To collect the qualitative data, the researcher used interview, observation, and documentation.Based on the result of the study, Teaching reading at the seventh grade students of SMP Advent Surakarta is quite good. The teacher could handle class well. It contain be known by the class situation. The students could be motivated by the teacher. But, teaching reading at the seventh grade students of SMP Advent Surakarta still had some problems of teaching learning process showed by still used the old methods and stuck on old text. From the teacher, she had limitation in method that she used. The teacher did not used special method while teaching reading. For the students, they could not used time wisely in reading activity. Some of students prefer to talk with their friends than doing reading activity. The technique of data analysis are data reduction, data display, and conclusion. Keywords: Teaching Learning Process, Teaching Reading, Descriptive Study.